Kualitas Hidup Individu dengan Gangguan Tiroid di Indonesia - Djawa, Kezia Raraseta; Hanami, Yuliana (Universitas Airlangga, 2024)
This study aims to explore the differences in quality of life (QoL) between hyperthyroidism and hypothyroidism in Indonesia. This study is a qualitative comparison, with the goal of identifying variations and similarities in the interpretation of QoL in each participants' experiences. Each group was interviewed based on QoL dimension in WHOQOL-BREF. Furthermore, interview transcript was analyzed by deductive thematic analysis. The results were compared across dimension, between the participant in each group, and it was found that there was predisposition to the same physical symptoms. Nevertheless, the causes of the disturbance in physical quality of the two groups were different, as well as the psychological symptoms. Positive social, environmental, and financial support play important roles in the QoL of both groups. Comorbidity became a differentiating factor in the physiological and psychological dynamics of participants in each group.